ANALYSIS OF INCOME DISPARITIES IN JAMBI PROVINCE 2010-2017 - Destiningsih, Rian; Sugiharti, Rr Retno; Achsa, Andhatu (Asosiasi Fakultas Ekonomi dan Bisnis Indonesia, 2019)
Economic growth does not reflect an increase in the welfare of society even though recorded in a high state. What occur now is economic growth is increase but disparities income is wider. The aims of this study to find out more about disparities income. This research used Williamson Index and Theil Entropy Index and focused in Jambi Province in term of time 2010 – 2017. Jambi Province's has unique and strategic location, which is near to the IMS-GT economic growth area (Indonesia, Malaysia, Singapore Growth Triangle). Because of the strategic location, Jambi Province should be able to achieve convergent conditions and become the highest Province in economic gain among others Province in Indonesia. However, in reality the economy state of Jambi province is opposite. The result of this research shows that Jambi Province's income disparity in 2010 - 2017 tends to decrease. But from the Williamson Index calculation, lifting income inequality in Jambi province in 2010-2017 is a high inequality, this can be concluded from the Williamson index value that’s more than 0.5. The main causes of disparity income in Jambi Province is differences in the structure of the economy. The difference in economic structure occurs due to differences in natural resources and human resources. In the other side, based on Theil Entropy Index it was concluded that inequality in Jambi Province in 2010-2017 was classified as low, because the index value was close to 0. JEL Classification: D30, D31, D33 Keywords: Disparities, Theil Entropy Index, Williamson Index